Stock‐Specific Size of Juvenile Sockeye Salmon in British Columbia Waters and the Gulf of Alaska. Issue 4 (16th June 2014) - Beacham, Terry D.; Beamish, Richard J.; Candy, John R.; Wallace, Colin; Tucker, Strahan; Moss, Jamal H.; Trudel, Marc
Abstract: The variation at 14 microsatellites was analyzed for 10, 500 juvenile Sockeye Salmon Oncorhynchus nerka obtained from coastal British Columbia and Gulf of Alaska surveys during 1996–2011. A 404‐population baseline was used to determine the individual identifications of the fish sampled, with individuals being identified to 47 populations or stocks of origin. Columbia River and Washington juveniles were consistently larger than those from British Columbia and Alaska. During July, larger individuals from the same Fraser River stock were observed in more northerly locations compared with those in the Strait of Georgia. There was a relationship between the timing of northward migration from the Strait of Georgia and juvenile body size, with individuals from larger populations or stocks migrating earlier than individuals from smaller stocks which remain resident for longer. There was a wide divergence among stocks in juvenile size and dispersion among sampling locations. Received August 1, 2013; accepted January 21, 2014